2007
DOI: 10.1021/bm060930w
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of Interaction of a Bioresponsive Endosomolytic Polyamidoamine with Interfaces. 1. Micelles as Model Surfaces

Abstract: Polymers are appealing as pH-responsive elements of multicomponent systems designed to promote cytosolic delivery of macromolecular drugs (including proteins and genes), but so far the delivery efficiency achieved has been relatively modest. Therefore, the aim of this study was to apply several physicochemical techniques that are well established in the colloid field (surface tension measurements, small-angle neutron scattering (SANS), and electron paramagnetic resonance (EPR)) to probe the mechanism of endoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
(57 reference statements)
1
19
0
Order By: Relevance
“…[9] Addition of bulky, non-ionic surfactant headgroups led to weaker interactions, and EPR confirmed that ISA23 Á HCl perturbed the micelle palisade layer leading to a decrease in fluidity of the interface with a lower degree of headgroup hydration, with a significant change in micelle morphology. Surprisingly, in these studies, [9] no interaction was seen at any pH (7.4-5.5) with globular, 1-palmitoyl-2-hydroxy-sn-glycero-3-phosphocholine (lyso-PC) micelles that are arguably a more biologically relevant model. These observations confirmed a complex pattern of ISA23/micelle interaction with both an electrostatic and a significant hydrophobic component.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…[9] Addition of bulky, non-ionic surfactant headgroups led to weaker interactions, and EPR confirmed that ISA23 Á HCl perturbed the micelle palisade layer leading to a decrease in fluidity of the interface with a lower degree of headgroup hydration, with a significant change in micelle morphology. Surprisingly, in these studies, [9] no interaction was seen at any pH (7.4-5.5) with globular, 1-palmitoyl-2-hydroxy-sn-glycero-3-phosphocholine (lyso-PC) micelles that are arguably a more biologically relevant model. These observations confirmed a complex pattern of ISA23/micelle interaction with both an electrostatic and a significant hydrophobic component.…”
Section: Introductionmentioning
confidence: 86%
“…[5,[7][8][9] Techniques more commonly applied in colloidal science such as pulsed-gradient spin-echo NMR, electron paramagnetic resonance (EPR) and small-angle neutron scattering (SANS) were used to study solution conformation and model surface interaction. Initial studies on the solution behavior of ISA23 Á HCl indicated a Gaussian-coil conformation with pH-induced coil expansion.…”
Section: Introductionmentioning
confidence: 99%
“…PAA shape, size, and pH-responsive changes in conformation were determined using small angle neutron scattering (SANS) [17,18], and the rate of diffusion in solution was defined using pulsed-gradient spin-echo NMR [17]. Most recently PAA interaction with model micelles [19], and model membranes whose composition was chosen to mimic the plasma, endosomal and lysosomal membrane was measured using surface tension and electron plasmon resonance techniques in combination with SANS [19].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study using small angle neutron scattering (SANS) suggested that this difference might be explained by different conjugates conformation 48. Such experiments have already shown the pH‐dependent changes in conformation of poly(amidoamine)s,20–22 experiments with the present conjugates could lead to further insight into the mechanism of Dox release.…”
Section: Resultsmentioning
confidence: 64%
“…Poly(amidoamine)s also present the advantage to degrade to oligomeric products in aqueous media within days or weeks, depending on their structures 18, 19. Owing to their capacity to undergo a conformational change from a coiled structure at pH = 7.4 to a more extended one when exposed to acidic pH,20–22 most recent effort have been directed to develop stimuli‐responsive constructs for biomacromolecules intracellular delivery 23–26. However, these polymers have also the potential to be used as drug carrier.…”
Section: Introductionmentioning
confidence: 99%